2018
DOI: 10.1016/j.jpainsymman.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Sedation for Existential Suffering: A Systematic Review of Argument-Based Ethics Literature

Abstract: There is a clear need to better define the terminology used in discussions of PS-ES and to ground ethical arguments in a more effective way. Anthropological presuppositions such as mind-body dualism underpin the debate and need to be more clearly elucidated using an interdisciplinary approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 78 publications
1
42
0
3
Order By: Relevance
“…A lack of robust conceptual and ethical arguments grounding PS-ES decision-making and practices clearly contributes to the controversial status of PS-ES and the absence of consensus among physicians 44. The abovementioned systematic review on ethical aspects of PS-ES14 revealed that implicit anthropological models and philosophical presuppositions underpin the ethical debate on PS-ES. However, considering the present systematic review of empirical evidence on physicians’ perceptions of PS-ES, it is revealed that philosophical presuppositions and ethical arguments remain mostly unclear and unexpressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of robust conceptual and ethical arguments grounding PS-ES decision-making and practices clearly contributes to the controversial status of PS-ES and the absence of consensus among physicians 44. The abovementioned systematic review on ethical aspects of PS-ES14 revealed that implicit anthropological models and philosophical presuppositions underpin the ethical debate on PS-ES. However, considering the present systematic review of empirical evidence on physicians’ perceptions of PS-ES, it is revealed that philosophical presuppositions and ethical arguments remain mostly unclear and unexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians have a primary, personal responsibility in clarifying the decision-making for patients, families and caregivers considering palliative sedation for existential suffering (PS-ES), and they play a key role in the discussions. A review of ethical aspects of PS-ES revealed that physicians’ anthropological models and philosophical presuppositions underpin the ethical debate on PS-ES 14…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, the controversy is centered on the questions of whether different types of suffering can be distinguished (e.g., if the differentiation between ''physical'' and ''psycho-existential'' suffering is assumed to be a valid distinction) and whether the different types of suffering can be skillfully addressed in (palliative) medicine. 13 The question of symptoms eligible for palliative sedation is linked to the one of prerogative of interpretation. This is because it is assumed that some types of suffering can be assessed better from the outside (i.e., by health care professionals) than others.…”
Section: Suffering: a Challenging Concept In Palliative Sedationmentioning
confidence: 99%
“…Though relatively straightforward to distinguish, actually defining each dimension of suffering has proved more difficult, and in point of fact, existential suffering has so far defied a universally accepted definition 3. The authors of a recent systemic review concluded that existential suffering continues to have multiple definitions and that moreover, opinions are divided as to its very nature 4. Most current definitions of existential suffering make some reference to mortality, loss of autonomy and meaninglessness of life as being important components and/or manifestations of this form of suffering but fall short of making the final connection with a clear definition 5 6.…”
Section: Introductionmentioning
confidence: 99%